PEMBUATAN KOMPOS JERAMI PADI PADA LAHAN SAWAH PETANI DI KOTA SOLOK UNTUK MENDUKUNG PROGRAM KETAHANAN PANGAN - Budi, Budi Santosa; Santosa, Budi; Anggraini, Okta Refi; Jannah, Hidayatul; Cinora, Cindi; Ulya, Rahmatul (Universitas Mataram, 2025)
ABSTACT The potential yield of rice paddy cultivated by farmers can still be increased if all farmers in Solok City use organic fertilizer according to the recommended rate of 5 tons/ha. Some members of the farmer group still burn rice straw after harvest, resulting in environmental pollution. The purpose of making rice straw compost is to improve and increase soil fertility by adding organic matter, gradually providing nutrients for plants, and reducing the use of chemical fertilizers, thereby saving farmers production costs and supporting sustainable agriculture. Furthermore, straw compost can improve soil health, water retention capacity, and encourage beneficial microbial activity, all of which support food security programs. Implementation methods include outreach, training, technology application, mentoring and evaluation, and program sustainability for partners in the multi-purpose farmer group in Tanah Garam Village, Solok City. Overall, the community service activities have successfully increased understanding and awareness of the use of rice straw for composting in farmers' rice fields in Solok City. The results of this activity are rice straw compost that can be directly used by farmers as organic fertilizer, to increase rice crop production and support food security programs. Keywords : compost, rice straw, rice fields, farmers, food security